(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
In this article, the author analyzes, from a biblical point of view, the ethical problem of civil disobedience. According with Romans 13:1-7, and 1 Peter 2:13-14, Christians have to be submitted to the human authorities, even if they are abusive or corrupt. The reason is that God, who is Sovereign, delegate some aspects of His rulership to human authorities. In the same time, because the human authorities are not infallible, they can promulgate laws that are contrary to the will of God, as it is revealed in the Bible. In certain cases, though Christians are submitted, they cannot obey to an unjust law. In Christian Ethics, there are two main positions: antipromulgation view and anticompulsion view. After the analyze of there two positions, the author concluded that Christians should use only non-violent methods in civil disobedience, and that the anticompulsion position is much better supported by the Word of God. Civil disobedience must be applied as a final solution when other actions failed.